Exploring the Effectiveness of Flipped Classroom Model in Teaching Writing to Senior High School Students in Riau - Rani Aulia Rayusda; Dian Pariska (Lembaga Yasin AlSys, 2026)
English writing instruction at the senior high school level continues to face challenges related to idea development, text organization, vocabulary use, language structure, and writing mechanics. This study aims to examine the effectiveness of the flipped classroom model in teaching writing to senior high school students in Riau. A quantitative approach with a quasi-experimental design was employed, involving 64 students divided into an experimental class and a control class. The sample was selected using cluster sampling based on existing classroom groups. Data were collected through writing pretests and posttests, and students’ writing performance was assessed using a rubric covering content, organization, vocabulary, language use, and mechanics. The data were analyzed using descriptive statistics, paired sample t-test, and independent sample t-test. The findings indicate that students in the experimental class achieved greater improvement in writing scores than those in the control class, with a significance value of 0.000. These results demonstrate that the flipped classroom model is effective in improving students’ writing ability. The study concludes that flipped classroom instruction can enhance writing learning by promoting active engagement, learner autonomy, and structured technology integration. This study contributes to English language teaching by providing empirical evidence on the effectiveness of flipped classroom pedagogy in senior high school writing instruction.